2021
DOI: 10.20944/preprints202101.0163.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cannabis Yield, Potency, and Leaf Photosynthesis Respond Differently to Increasing Light Levels in an Indoor Environment

Abstract: Since the recent legalization of medical and recreational use of cannabis (Cannabis sativa L.) in many regions worldwide, there has been high demand for research to improve yield and quality. With the paucity of scientific literature on the topic, this study investigated the relationships between light intensity (LI) and photosynthesis, inflorescence yield, and inflorescence quality of cannabis grown in an indoor environment. After growing vegetatively for 2 weeks under a canopy-level photosynthetic photon flu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…However, the present study observed a 24% increase in area-based chlorophyll content, which may indicate that cannabis favours upregulating photosynthetic capacity (i.e., maximizing resource utilization) over the common foliar morphology-based adaptive responses to high light stress. Clonal cannabis' very high photosynthetic capacity (Chandra et al, 2008;Rodriguez-Morrison et al, 2021) appears to be present even at the relatively young vegetative stage (Chandra et al, 2015). In the context of indoor production, the reduction in individual leaf area with increasing LI may also confer an increase in whole-plant net photosynthesis, since a greater proportion of the incident PAR should penetrate deeper into the canopy through inherent reductions in self-shading.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the present study observed a 24% increase in area-based chlorophyll content, which may indicate that cannabis favours upregulating photosynthetic capacity (i.e., maximizing resource utilization) over the common foliar morphology-based adaptive responses to high light stress. Clonal cannabis' very high photosynthetic capacity (Chandra et al, 2008;Rodriguez-Morrison et al, 2021) appears to be present even at the relatively young vegetative stage (Chandra et al, 2015). In the context of indoor production, the reduction in individual leaf area with increasing LI may also confer an increase in whole-plant net photosynthesis, since a greater proportion of the incident PAR should penetrate deeper into the canopy through inherent reductions in self-shading.…”
Section: Discussionmentioning
confidence: 99%
“…Following initial setup, the PPFD at the top of each plant was measured and recorded twice weekly using a quantum sensor (LI-180; LI-COR Biosciences, Lincoln, NE, USA), and the fixture hang-heights were adjusted accordingly, to maintain consistent canopy-level PPFDs throughout the trial. Although the layout of the experiment was a RCBD, the trial was conducted as a gradient design (Jones-Baumgardt et al, 2020;Rodriguez-Morrison et al, 2021) with each plant treated as an experimental unit and assigned a LI level consistent with their respective accumulated light histories. To this end, the average PPFD (APPFD) each individual plant received over the trial was obtained by computing the light integrals between each bi-weekly PPFD measurement period, summing these integrals over the entire trial to determine a total light integral (TLI, mol•m -2 ), and then back-calculating to determine APPFD by dividing TLI by the total number of seconds of lighting during the trial (i.e., 3600 s•hr -1 × 16 hr Ruter, 1992).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations